Protection of indigenous peoples' right in Malaysia state's perspective, obligation and capacity - Rohaida Nordin (Penerbit Universiti Kebangsaan Malaysia, 2019)
Discussion in this book considers the perspective and ideology of the Malaysian government towards human rights. With regard to sovereignty, the Malaysian government views that the issue of the protection of indigenous peoples' rights, or any other human rights in general, is a domestic issue within its exclusive control. Despite its existing human rights ideology, Malaysia may be said to have legal obligations, under either treaties or customary international law, to observe international standards, including any obligations and commitments that have been made by Malaysia under the UN Charters. However, the ability of Malaysia to effectively discharge its responsibilities and observe its obligations in the area of human rights depends predominantly on the strength of its domestic institutions, the judiciary, executive and legislature. This book demonstrates the importance of the State government to have the capacity building and resources, and political will to adopt and implement any international human rights standards or even to implement any of its domestic laws and policies.